Sexual Behaviour and Risks of HIV Infection - Michel Hubert (Presses de l'Université Saint-Louis, 1990)
The Centre d'études sociologiques of the Facultés universitaires Saint-Louis has been selected to participate in the 4th Medical and Health Research Programme of the European Communities by launching a «concerted action» programme on «Sexual Behaviour and Risks of HIV Infection». These are the proceedings of a workshop that was held in Brussels on 5 to 7 April 1989. Its objectives were to discuss with representatives from about twenty potential collaborating centres a proposal for a concerted action programme and to engage in preliminary scientific exchanges on the main aspects of the proposed research programme.